2021
DOI: 10.1093/ajcn/nqaa336
|View full text |Cite
|
Sign up to set email alerts
|

Diet and physical activity during the coronavirus disease 2019 (COVID-19) lockdown (March–May 2020): results from the French NutriNet-Santé cohort study

Abstract: Background Since December 2019, coronavirus disease 2019 (COVID-19) has been spreading steadily, resulting in overwhelmed health-care systems and numerous deaths worldwide. To counter these outcomes, many countries, including France, put in place strict lockdown measures, requiring the temporary closure of all but essential places and causing an unprecedented disruption of daily life. Objectives Our objective was to explore p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
337
13
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(411 citation statements)
references
References 57 publications
38
337
13
23
Order By: Relevance
“…Appetizer purchases nearly doubled between January (12.8 g/person/day) and April 2020 (22.1 g/person/day), in contrast to the same period of 2019, when they remained constant (January 12.2 g and April 13.8 g/person/day). An increase in the consumption of appetizers was also observed in other Spanish studies carried out during the lockdown [ 19 ], as well as in other countries such as Poland [ 31 ], Italy [ 12 ] or France [ 32 ], although other studies found no change or even decreases [ 33 ]. This increment in the purchase of appetizers is probably due to the desire to continue with some socialization habits that people did outdoors before the pandemic [ 28 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Appetizer purchases nearly doubled between January (12.8 g/person/day) and April 2020 (22.1 g/person/day), in contrast to the same period of 2019, when they remained constant (January 12.2 g and April 13.8 g/person/day). An increase in the consumption of appetizers was also observed in other Spanish studies carried out during the lockdown [ 19 ], as well as in other countries such as Poland [ 31 ], Italy [ 12 ] or France [ 32 ], although other studies found no change or even decreases [ 33 ]. This increment in the purchase of appetizers is probably due to the desire to continue with some socialization habits that people did outdoors before the pandemic [ 28 ].…”
Section: Discussionsupporting
confidence: 63%
“…To our knowledge, few studies have assessed changes in energy values during the pandemic. In the NutriNet-Santé cohort, a reduction in energy values was found with respect to estimates from 2017 to 2019 [ 32 ]. More studies would be needed to assess whether there are some common patterns associated with lockdowns, or, on the contrary, whether changes are country- or even region-specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, trends toward unfavourable dietary behaviours during the lockdown, such as increased caloric intake, reduced consumption of fruits and vegetables, and weight gain study was reported. 42 , 43 In contrary to our findings, a study in the United Arab Emirates (UAE) reported a shift towards unhealthy dietary patterns among participants during the pandemic. 44 In addition to physical exhaustion, emotional exhaustion, irritability, tension and sleeping disturbances have been reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies reported changes in university students' lifestyles that occurred during home confinement caused by the pandemic [5][6][7][8] but, to our knowledge, no studies have analyzed the lifestyles of these students both before and during the COVID-19 pandemic. Because the return to normal daily living may take some time, understanding the influence that the pandemic exerted on the lifestyles of university students, in particular those enrolled in health sciences programs, may inform strategies to promote their well-being.…”
Section: Introductionmentioning
confidence: 99%